2013
DOI: 10.1117/12.2008100
|View full text |Cite
|
Sign up to set email alerts
|

Improved multimodal biomarkers for Alzheimer's disease and mild cognitive impairment diagnosis: data from ADNI

Abstract: The accurate diagnosis of Alzheimer's disease (AD) and mild cognitive impairment (MCI) confers many clinical research and patient care benefits. Studies have shown that multimodal biomarkers provide better diagnosis accuracy of AD and MCI than unimodal biomarkers, but their construction has been based on traditional statistical approaches. The objective of this work was the creation of accurate AD and MCI diagnostic multimodal biomarkers using advanced bioinformatics tools. The biomarkers were created by explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The segmentation masks were provided by Heckemann et al 13 using multiatlas propagation enhanced registration, an automatic whole-brain multiregion segmentation method. In order to continue studying the same population as in previous works, 14 only data and images uploaded up to June 2012 were considered. The 98 MCI subjects studied in such works were considered for this study, where those with a reported progression to AD within the 24 months following their baseline visit (BL) were considered as cases and those who maintained a cognitive stability during the same period of time were considered as controls.…”
Section: Methodsmentioning
confidence: 99%
“…The segmentation masks were provided by Heckemann et al 13 using multiatlas propagation enhanced registration, an automatic whole-brain multiregion segmentation method. In order to continue studying the same population as in previous works, 14 only data and images uploaded up to June 2012 were considered. The 98 MCI subjects studied in such works were considered for this study, where those with a reported progression to AD within the 24 months following their baseline visit (BL) were considered as cases and those who maintained a cognitive stability during the same period of time were considered as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Features that statistically describe sound waves have previously been found to be of importance in solving similar problems [22]. Thus, the 16 statistical features listed in the following list were extracted from each sample.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Our objective was to determine whether multimodal and nonpreviously AD associated features could improve the classification accuracy between subjects with AD, MCI, and healthy controls (HC), building on preliminary versions [28]. …”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we explore additional information from imaging sources (e.g., cortical thickness and hypometabolic convergence index), biological tests (e.g., complement component 3 concentrations and TOMM40 poly-T variable length), and clinical records (e.g., blood pressure, drug sensitivities, and presence of a depressed mood). Our objective was to determine whether multimodal and nonpreviously AD associated features could improve the classification accuracy between subjects with AD, MCI, and healthy controls (HC), building on preliminary versions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%